2017
DOI: 10.1080/21580103.2017.1387613
|View full text |Cite
|
Sign up to set email alerts
|

Forest users’ level of participation in a participatory forest management program in southwestern Ethiopia

Abstract: This study examines the level of forest users' participation at different stages of a participatory forest management (PFM) program, and identifies factors that influence their level of participation in the Gebradima forest, southwest Ethiopia. Data were collected from five forest user groups (FUGs) through household surveys, key informant interviews, and focus group discussions. A participation index (PI) and binary logistic regression model were used to analyze the data. Results revealed that the level of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…354.38$) (see Table 3). Our findings supported Tadesse et al (2017), who emphasized that income from forest products and services was significant to rural households. These authors claimed that once rural people earned or benefitted more from forests, they might participate in Lerman (1985); Adams (1994); Babulo et al (2009); Fonta and Ayuk (2013) and Angelsen et al (2014).…”
Section: Income Diversity In Rural Householdssupporting
confidence: 89%
See 1 more Smart Citation
“…354.38$) (see Table 3). Our findings supported Tadesse et al (2017), who emphasized that income from forest products and services was significant to rural households. These authors claimed that once rural people earned or benefitted more from forests, they might participate in Lerman (1985); Adams (1994); Babulo et al (2009); Fonta and Ayuk (2013) and Angelsen et al (2014).…”
Section: Income Diversity In Rural Householdssupporting
confidence: 89%
“…This requires them to implement policies and national plans of action, build capacity and arrange their national institutions accordingly. Even if some of those governments seemed to have the capacity to manage their forests, empirical studies have documented that degradation continues in practice as many developing countries have weak control over forestry and poor rural livelihood strategies (Arnold 1991;Manandhar and Shin 2013;Tadesse et al 2017;FAO 2018;Nhem et al 2018). There is still extreme rural poverty: The World Bank (2016, p.5) reported that 10.7% of the world's population lived on less than 1.90$a day in 2013.…”
Section: The Relationship Between Forest Resources Rural Livelihoodsmentioning
confidence: 99%
“…Education catalyzes the process of information and knowledge flow thus enabling the educated community members to participate in management. Several other studies have also shown that respondents with larger families participated more in community forest management and those without formal education showed low levels of participation in Nepal, Haiti, and Ethiopia, respectively [51][52][53]. On the other hand, age was negatively and significantly correlated to participation in the forest management program.…”
Section: Community Involvement In Forest Managementmentioning
confidence: 87%
“…There is little published on how far policy promotes women's participation in sustainable forestry in Cambodia but a recent study indicated that policymakers either lack the knowledge or attention to create opportunities for women (Allendort & Allendort 2013). Evans et al (2017) and Tadesse et al (2017) concluded that women face significant obstacles to effective participation in forest decision-making at the community level. Following these, they felt that addressing rights, allocating authority and setting an employment quota for women in the forest sector, would enhance their participation.…”
Section: Barriers Preventing Women From Participating Effectively In mentioning
confidence: 99%